Farmers’ and millers’ experiences and attitudes towards the production and processing of zinc biofortified wheat in Pakistan: a mixed methods study - Ceballos-Rasgado, Marena; Ajmal, Subhan; Mahboob, Usman; Ander, E. Louise; Zia, Munir; Moran, Victoria Hall; Joy, Edward J. M.; Zaman, Mukhtiar; Ohly, Heather; Lowe, Nicola M. (Frontiers in Nutrition, 2023)
Background: Zinc biofortified wheat may be a sustainable strategy to increase zinc intake in areas where fortification and dietary diversification are not feasible or are limited by household purchasing power. This convergent mixed methods study aimed to explore the farmers' and millers' experiences and attitudes towards the production and processing of zinc biofortified wheat in Pakistan.A telephone survey was conducted with farmers (N=418) who were provided with Zincol-2016 biofortified wheat seed for the 2019-2020 growing season, as part of a wheat grain micronutrient mapping study across Punjab Province. The survey explored the farmers' experiences of growing Zincol-2016 and whether they opted to grow it again in the subsequent season. Semistructured focus group discussions were undertaken in a separate group of farmers in Khyber Pakhtunkhwa (KP) province (N=12) who grew Zincol-2016 for the BiZiFED2 RCT. Millers were also interviewed in KP, both those who had processed Zincol-2016 for the trial (N=12) and those who had no experience of processing biofortified wheat (N=12). Survey data were analyzed using descriptive statistics and transcripts of focus groups were analyzed using thematic analysis.Results: Nearly half of farmers who responded to the survey (47%) re-cultivated Zincol-2016 in the following season. The drivers for Zincol-2016 re-cultivation were seed availability (100%), grain yield and growth resistance (98%), quality of the flour from the previous harvest (97%) and nutritional benefit (94.5%). Discussions with farmers suggested that the main motivators for potential This is a provisional file, not the final typeset article scale-up of biofortified wheat were the perceived quality of the grain, wheat, and flour. Millers saw it as an opportunity to expand their business. Farmers and millers valued the health benefits of the wheat. Challenges for scale-up include the need of additional support to produce it, unfamiliarity with the biofortification process, production costs, and external threats to the supply chain.Farmers and millers showed a strong implicit preference for Zincol-2016 over alternative varieties. Crop performance and product yield were the most cited motivators for growing Zincol-2016. Farmers and millers are willing to produce and process biofortified wheat if financial and educational support is provided.